2005
DOI: 10.1186/1479-5876-3-31
|View full text |Cite
|
Sign up to set email alerts
|

A quest for therapeutic antigens in bone and soft tissue sarcoma

Abstract: Over the past three decades, there have been remarkable advances in the treatment of bone and soft tissue sarcomas. These include the introduction of adjuvant chemotherapy, establishment of guidelines for adequate surgical margins, and the development of post-excision reconstruction. There have also been advances in the field of immunotherapy against bone and soft tissue sarcomas, which, unfortunately, have received less attention. However, lack of progress in chemotherapybased treatments for bone and soft tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The absence of information about the natural variability of tetramer-positive cells in patients, the low frequencies of tetramer-positive cells, and the absence of replicate analyses further suggests that tetramer-positive cells might not have been elicited with vaccination. A similar result and interpretation was found in the previous trial conducted by this group, in which they commented that other measures of immune response should be conducted in the future, such as by IFN-γ ELISPOT [4]. However, no other measures of immune response were employed in the current trial.…”
Section: Expert Commentarysupporting
confidence: 80%
See 2 more Smart Citations
“…The absence of information about the natural variability of tetramer-positive cells in patients, the low frequencies of tetramer-positive cells, and the absence of replicate analyses further suggests that tetramer-positive cells might not have been elicited with vaccination. A similar result and interpretation was found in the previous trial conducted by this group, in which they commented that other measures of immune response should be conducted in the future, such as by IFN-γ ELISPOT [4]. However, no other measures of immune response were employed in the current trial.…”
Section: Expert Commentarysupporting
confidence: 80%
“…No DTH responses were detected, a technique commonly used to detect memory T-cell immune responses elicited by peptide vaccines [9–11]. The absence of DTH responses to the native epitope in the current and previous [4] trials suggests memory-type responses were not elicited. In addition, the tetramer analysis was not uniformly conducted, making it impossible to compare results among treatment groups.…”
Section: Expert Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Although most Ewing sarcoma tumors show only little infiltration by lymphocytes [ 37 ], the fact that BCL11B is expressed in normal T cells ( Supplementary Figure 2 ) should be taken into account when assessing immunoreactivity in small-round-cell tumors. In indeterminate cases, a CD3 staining may be helpful ( Supplementary Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence for both spontaneous regression as well-efficient immunosurveillance in sarcoma, prompting investigators to explore immunotherapy as a treatment modality (6,7). Recently, several clinical trials have included sarcoma patients in the testing of various immunotherapy strategies, including: (i) immune checkpoint blockade (8)(9)(10); (ii) tumorspecific or tumor-associated peptide vaccines (11)(12)(13)(14); and (iii) adoptive immune cell therapies with allogeneic NK cells (ongoing clinical trials), autologous T cells (15), CAR-T cells (ongoing clinical trials) and NY-ESO-1-specific T cells (16) to name a few (17). However, these studies aim to target general tumor markers found in a variety of solid tumors and hematological malignancies, not specifically targeting sarcomas.…”
Section: Introductionmentioning
confidence: 99%